INSTRUCTIONAL MEDIA BOOKLET ON BIODIVERSITY BASED ON THE IDENTIFICATION OF FERN PLANTS IN THE KUMAYAN ISLAND TOURISM PARK AREA, BENGKULU CITY - Kasrina, Kasrina; Inayah, Inayah; Abas, Abas; Ekaputri, Rendi Zulni; Yennita, Yennita; Hidayat, Syarif (Universitas Negeri Makassar, 2024)
This research aims to develop open media in a booklet on diversity of ferns in Taman Wisata Pulau Kumayan Bengkulu City for class X SMA. This is Research and Development (R&D) with the Borg and Gall model which is limited to stage 5, namely stage (1) Research and initial information gathering, (2) Planning, (3) Initial product development, (4) Initial Field Trials Stage, and (5) Main Product Revision Phase. Sampling of ferns using the exploration method was carried out at the Taman Wisata Pulau Kumayan Bengkulu Bengkulu City. The booklet suitability test was carried out by material expert validators, media experts and practitioner experts (teachers), and the readability test was carried out by 30 class X students at SMAN 8 Bengkulu City. The results show types of ferns found in Taman Wisata Pulau Kumayan Bengkulu City numbered 10 families, with 15 types. The Eligibility Booklet received very appropriate criteria with a validation percentage of material experts 95.8%, media experts 87.5% and practitioner experts 93.75%. The percentage of students' readability tests on the booklet s developed received very good criteria by obtaining a score based on the presentation aspect of 98%, material 92%, and benefits 95% in the decent category.